Respostas
respondido por:
0
Bom dia.
veja:
m + j = 700
m = j + 120
substitui o valor de m da segunda equação na primeira equação
j + 120 + j = 700
2j = 700 - 120
j = 580 / 2
j = 290
m = j + 120
m = 290 + 120
m = 410
Marcos tem R$ 410,00 e João tem R$ 290,00
veja:
m + j = 700
m = j + 120
substitui o valor de m da segunda equação na primeira equação
j + 120 + j = 700
2j = 700 - 120
j = 580 / 2
j = 290
m = j + 120
m = 290 + 120
m = 410
Marcos tem R$ 410,00 e João tem R$ 290,00
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás